PELATIHAN KETRAMPILAN KERJA BAGI ANGKATAN KERJA USIA PRODUKTIF - Tri Yulistyawati Evelina; Yosi Afandi (Publisher UPT P2M Politeknik Negeri Malang, 2016)
The purpose of this service activities is to reveal data about the process of empowerment of labor force age group earning through vocational skills training. While the benefits as input to develop a workforce empowerment program carried out by the productive age Karangtaruna manager.Based on the method of PKM taken to address the problem, namely: (1) Pre Training, by identifying existing resources, further proposes establishment will be appointed as a pilot project, (2) Design training, the training according to the recommendations proposed (3) Implementation of vocational skills training. Job training recommended by the Board of Karang Taruna RW. 14 is a Digital Printing with training materials (1) Digital Printing & Design products, (2) Practice of Product Design Using Photoshop application, (3) Practice print media design results in t-shirts.